Introduction of a guideline for measurements of greenhouse gas fluxes from soils using non‐steady‐state chambers. Issue 4 (29th June 2022) - Maier, Martin; Weber, Tobias K. D.; Fiedler, Jan; Fuß, Roland; Glatzel, Stephan; Huth, Vytas; Jordan, Sabine; Jurasinski, Gerald; Kutzbach, Lars; Schäfer, Klaus; Weymann, Daniel; Hagemann, Ulrike
Abstract: Soils represent a major global source and sink of greenhouse gases (GHGs). Many studies of GHG fluxes between soil, plant and atmosphere rely on chamber measurements. Different chamber techniques have been developed over the last decades, each characterised by different requirements and limitations. In this manuscript, we focus on the non‐steady‐state technique which is widely used for manual measurements but also in automatic systems. Although the measurement method appears very simple, experience gained over the years shows that there are many details which have to be taken into account to obtain reliable measurement results. This manuscript aims to share lessons learnt and pass on experiences in order to assist the reader with possible questions or unexpected challenges, ranging from the planning of the design of studies and chambers to the practical handling of the chambers and the quality assurance of the gas and data analysis. This concise introduction refers to a more extensive Best Practice Guideline initiated by the Working Group Soil Gases ( AG Bodengase ) of the German Soil Science Society ( Deutsche Bodenkundliche Gesellschaft ). The intention was to collect and aggregate the expertise of different working groups in the research field. As a compendium, this Best Practice Guideline is intended to help both beginners and experts to meet the practical and theoretical challenges of measuring soil gas fluxes with non‐steady‐state chamber systems and to improve the quality of the individual flux measurements and thus entire GHG studies by reducing sources of uncertainty and error.